Pottery Assemblages from Vodoba II Settlement in the Light of Ideas about the Early Iron Age in Lake Beloye Region - Novikov Alexander V. (Поволжская археология, 2024)
The paper deals with the analysis of materials from the Vodoba II settlement that demonstrates a complicated process of development of Late Kargopol antiquities nearby Lake Beloye. The discovered pottery assemblages are syncretic. Several types of ceramics are distinguished: textile, brushed, smoothed with impressions of a comb stamp, ceramics of the Vyatka-Vetluga culture of the Ananyino cultural and historical area (ACHA) and hybrid. It is this combination in ceramic sets from ancient settlements that determines the specificity of Late Kargopol antiquities. Two major stages in the development of settlements in this region are identified: the first one corresponds to the first half of the I millennium BC, the second one is accompanied by the spread of the bearers of cultural traditions of the VyatkaVetluga culture ACHA and the development of hybrid shapes of pottery in the settlements (up to the 3rd century BC) in these areas in the middle of the I millennium BC. At the second stage Lake Beloye area settlements are included in a large "hybrid world" with ceramics of close types, having a certain originality in different regions, which is primarily associated with the traditions of pottery assemblages formation in the previous periods.